Pengaruh Marketing Mix dan Patient Experience Melalui Kepuasan Terhadap Loyalitas Pasien Umum di Instalasi Rawat Inap Rumah Sakit Stella Maris Makassar Tahun 2022 - Mene Paradilla; Nur Miftahul Janna (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
In maintaining patient loyalty, one of the marketing strategies that can be done is Marketing Mix. The marketing mix is ​​a set of marketing tools used to achieve marketing objectives in the target market. The elements are interrelated, blended and used appropriately so that the company can achieve effective marketing goals and satisfy consumer needs. the marketing mix can improve the perceived quality of the patient's condition of a service. If the patient's perception of the services provided by the hospital is good, then the patient's experience (patient experience) towards the hospital will be positive where consumer expectations will be their previous purchase experience. This condition can increase patient satisfaction, which continues in the formation of patient loyalty. This study aims to analyze the influence of the marketing mix and patient experience based on general patient loyalty in the inpatient installation of Stella Maris Hospital Makassar. This type of research is a quantitative study using an observational study with a cross sectional study design. The sample in this study was 358 general patients at the Stella Maris Hospital Makassar. The results showed that the marketing mix, patient experience through satisfaction had a significant effect on patient loyalty at Stella Maris Hospital Makassar.